2008
DOI: 10.1007/s00520-008-0446-9
|View full text |Cite
|
Sign up to set email alerts
|

Causal attributions to epidemiological risk factors and their associations to later psychological adjustment among Japanese breast cancer patients

Abstract: The current study indicates that forming causal attributions influences the adjustment to the illness in Japanese breast cancer patients and attributions to certain risk factors for breast cancer may contribute to better adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…They also expressed the stigma that they felt when a diagnosis of cancer was interpreted as "karma" or punishment for their sins by other people who live in their community. Conversely, Oba et al, [35] found that Japanese women who did not identify themselves with a particular religion, did not believe God's will was a cause of their cancer.Previous injury. In nine out of the 24 studies reviewed, participants cited a 'blow' to the breast or previous injury as a cause of their breast cancer [9,13,15,24,[35][36][37][38]42].…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…They also expressed the stigma that they felt when a diagnosis of cancer was interpreted as "karma" or punishment for their sins by other people who live in their community. Conversely, Oba et al, [35] found that Japanese women who did not identify themselves with a particular religion, did not believe God's will was a cause of their cancer.Previous injury. In nine out of the 24 studies reviewed, participants cited a 'blow' to the breast or previous injury as a cause of their breast cancer [9,13,15,24,[35][36][37][38]42].…”
mentioning
confidence: 98%
“…Conversely, Oba et al, [35] found that Japanese women who did not identify themselves with a particular religion, did not believe God's will was a cause of their cancer.…”
mentioning
confidence: 98%
See 3 more Smart Citations